2011
DOI: 10.1097/qai.0b013e3181f7f61a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Inflammatory and Coagulation Biomarkers: A Randomized Comparison of Immediate versus Deferred Antiretroviral Therapy in Patients With HIV Infection

Abstract: Ojectives Among a subgroup of participants in the Strategies for Management of Antiretroviral Therapy (SMART) Trial that were naïve to antiretroviral therapy (ART) or off ART (≥6 months) at study entry, risk of AIDS and serious non-AIDS events was increased for participants who deferred ART compared to those randomized to (re)initiate ART immediately. Our objective was to determine whether ART initiation in this group reduced markers of inflammation and coagulation that have been associated with increased mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 41 publications
10
128
2
Order By: Relevance
“…[42][43][44][45] Our findings corroborate another recent analysis, which reported that only d-dimer, and not IL-6 or hs-CRP, is reduced over the short term in those initiating ARV therapy. 46 Additionally, the reductions in LPS observed here are similar in magnitude to those seen in a previous study 47 ; the similar reductions in the DRV/r and ATV/r arms suggest that these ARV agents do not result in differential levels of LPS, a trigger of persistent immune activation in ARV-treated individuals. In contrast, no decreases in hs-CRP were seen in either arm of this study over 48 weeks; this observation is in agreement with the ACTG (AIDS Clinical Trials Group) A5095 study, which demonstrated similar results in subjects receiving efavirenzbased regimens over 96 weeks.…”
Section: Discussionsupporting
confidence: 71%
“…[42][43][44][45] Our findings corroborate another recent analysis, which reported that only d-dimer, and not IL-6 or hs-CRP, is reduced over the short term in those initiating ARV therapy. 46 Additionally, the reductions in LPS observed here are similar in magnitude to those seen in a previous study 47 ; the similar reductions in the DRV/r and ATV/r arms suggest that these ARV agents do not result in differential levels of LPS, a trigger of persistent immune activation in ARV-treated individuals. In contrast, no decreases in hs-CRP were seen in either arm of this study over 48 weeks; this observation is in agreement with the ACTG (AIDS Clinical Trials Group) A5095 study, which demonstrated similar results in subjects receiving efavirenzbased regimens over 96 weeks.…”
Section: Discussionsupporting
confidence: 71%
“…In patients who delay antiretroviral therapy, there was an expected rise in CD4 + T cells on initiation of antiretroviral therapy. Although there was also a decrease in the level of D-dimer, there was no change in elevated IL-6 or CRP (52). It is presently unclear whether the decrease in D-dimer will reduce clinical disease; however, the continued elevated IL-6 and CRP levels indicate a continued inflammatory state, even in patients being successfully treated with antiretroviral therapy and who sustain an increased risk for non-HIV-1-associated death.…”
Section: Study Design Of New Hdac Inhibitors In Hiv-1 Purgingmentioning
confidence: 82%
“…Because cART improves immune function, lowers HIV viral load, and reduces inflammation [29], earlier cART initiation had previously been proposed as an approach to reduce cancer risk among HIV-infected persons [2][3][4]. Furthermore, cohort studies had long identified a relationship between immunodeficiency and uncontrolled HIV RNA replication with risk of nonHodgkin lymphoma and Kaposi sarcoma [1,2].…”
Section: Discussionmentioning
confidence: 99%